2023
DOI: 10.1021/jacs.2c13149
|View full text |Cite
|
Sign up to set email alerts
|

Safe, One-Pot, Homogeneous Direct Synthesis of H2O2

Abstract: Hydrogen peroxide is an environmentally friendly oxidizing agent but current synthetic methods are wasteful. This is a result of the high flammability of H 2 /O 2 mixtures and/or the requirement for cocatalysts. In this paper, we report the synthesis of H 2 O 2 by means of a homogeneous catalyst, which allows a safe, one-pot synthesis in water, using only H 2 and O 2 . This catalyst is capable of removing electrons from H 2 , storing them for the reduction of O 2 , and then permitting the protonation of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…114 A Rh(II) dimer complex (1) was recently reported to act as an efficient catalyst for the direct synthesis of H 2 O 2 from H 2 and O 2 in water (Scheme 7). 115 1 is reduced to two equivalents of the Rh(I) complex ( 2) by H 2 and the Rh(I) complex then reduces O 2 to H 2 O 2 in the presence of CH 3 COOH (Scheme 7). 115 The maximum TON was determined to be 910 under an H 2 /O 2 (95/5) atmosphere (1.9 MPa) at 23 °C for 12 h, which is the highest TON in the direct synthesis of H 2 O 2 from H 2 and O 2 using a homogeneous catalyst.…”
Section: Hydrogen Peroxidementioning
confidence: 99%
See 1 more Smart Citation
“…114 A Rh(II) dimer complex (1) was recently reported to act as an efficient catalyst for the direct synthesis of H 2 O 2 from H 2 and O 2 in water (Scheme 7). 115 1 is reduced to two equivalents of the Rh(I) complex ( 2) by H 2 and the Rh(I) complex then reduces O 2 to H 2 O 2 in the presence of CH 3 COOH (Scheme 7). 115 The maximum TON was determined to be 910 under an H 2 /O 2 (95/5) atmosphere (1.9 MPa) at 23 °C for 12 h, which is the highest TON in the direct synthesis of H 2 O 2 from H 2 and O 2 using a homogeneous catalyst.…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…115 1 is reduced to two equivalents of the Rh(I) complex ( 2) by H 2 and the Rh(I) complex then reduces O 2 to H 2 O 2 in the presence of CH 3 COOH (Scheme 7). 115 The maximum TON was determined to be 910 under an H 2 /O 2 (95/5) atmosphere (1.9 MPa) at 23 °C for 12 h, which is the highest TON in the direct synthesis of H 2 O 2 from H 2 and O 2 using a homogeneous catalyst. 114,116 In 2013, it was reported that H 2 O 2 was produced from H 2 O and O 2 without any sacrificial electron donor as shown in Scheme 8.…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…While employed industrially on a large scale, there are several drawbacks to the anthraquinone process including the flammable nature of H 2 /O 2 , the corresponding requirement for stepwise reactions, as well as the use of currently petroleum-derived H 2 . These shortcomings have spurred a great deal of investigation into alternative synthetic routes for H 2 O 2 production, with some exciting developments in recent years. Still, many of the best catalysts use precious metals, forcing conditions, or require separation between O 2 and H 2 cycling. The use of abundant metal catalysts would be advantageous due to cost and scarcity, but examples using first-row transition metals are limited …”
Section: Introductionmentioning
confidence: 99%
“…H 2 ase is an enzyme that activates H 2 as an energy source at room temperature, 10,11 and we have made a series of model compounds that mimic such behavior. [12][13][14][15][16][17][18][19] This has led us to produce potential H 2 -derived energy carriers (H 2 ECs) with all the requirements.…”
mentioning
confidence: 99%
“…The extraction of the electron from H 2 has been performed at room temperature by using hydrogenase model complexes (Table S2, ESI †). [12][13][14]16,18,19,[23][24][25][26] Although the extracted electrons have been used for the reduction of the ferrocenium ion, Cu II , O 2 or organic halides at room temperature, there was no example of the reduction of CO 2 at room temperature (Table S2, ESI †).…”
mentioning
confidence: 99%